1675. Activity of Gepotidacin Against Escherichia coli Isolates from Community-acquired Urinary Tract Infections Collected Between 2019-2021 in the United States. (15th December 2022) - Arends, S J R yan; Butler, Deborah; Scangarella-Oman, Nicole E; Tholen, Lindsey; Streit, Jennifer M; Mendes, Rodrigo E
Abstract: Background: Gepotidacin is a novel, bactericidal, first-in-class triazaacenaphthylene antibiotic that inhibits bacterial DNA replication by a distinct mechanism of action that confers activity against most strains of target pathogens, such as Escherichia coli, Staphylococcus saprophyticus, and Neisseria gonorrhoeae, including those resistant to current antibiotics. This study reports on the in vitro activity of gepotidacin and other oral antibiotics tested against E. coli clinical isolates collected from patients with UTIs for a gepotidacin UTI global surveillance study as part of the SENTRY Antimicrobial Surveillance Program. Methods: A total of 1, 978 E. coli isolates were collected between 2019-2021 from 47 medical centers within the US. All isolates were cultured from urine specimens collected from patients seen in emergency and outpatient medical services representative of community-acquired infections. Bacterial identifications were confirmed by MALDI-TOF. Isolates were tested for susceptibility by CLSI methods at a central laboratory (JMI Laboratories). MIC results for oral antibiotics licensed for the treatment of uUTI, multidrug-resistant (MDR), and extended-spectrum β-lactamase (ESBL) subsets were interpreted per CLSI criteria. Results: Gepotidacin (MIC50 /90, 2/4 mg/L) displayed good activity against 1, 978 E. coli isolates, with 98.3% of all observed gepotidacin MICs ≤4 mg/L (Table). Susceptibility (S) rates for other oral agents tested against these isolates were: amoxicillin-clavulanate (83.7%S), ampicillin (50.9%S), ciprofloxacin (79.1%S), fosfomycin (99.7%S), mecillinam (94.2%S), nitrofurantoin (98.2%S), and trimethoprim-sulfamethoxazole (71.3%S). When tested against the drug-resistant subsets, gepotidacin maintained similar MIC50/90 values (1-2/4 mg/L). Gepotidacin was also active against ESBL and MDR E. coli isolates, inhibiting 94.7% and 95.9%, respectively, at gepotidacin concentrations ≤ 4 mg/L. Conclusion: Gepotidacin demonstrated potent in vitro activity against contemporary community-acquired E. coli urine isolates. This activity was maintained among isolates demonstrating resistance to other oral standard of care antibiotics including ESBL, FQ-R, and MDR E. coli. Disclosures: SJ Ryan Arends, PhD, AbbVie: Grant/Research Support|GSK: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Shionogi: Grant/Research Support Nicole E. Scangarella-Oman, MS, GlaxoSmithKline plc.: Employee and shareholder Lindsey Tholen, BS (ASCP), GSK: Board Member|GSK: work for hire|Shionogi: Grant/Research Support Jennifer M. Streit, BS, MT(ASCP), Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Shionogi: Grant/Research Support Rodrigo E. Mendes, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Office for Assistant Secretary of Defense for Health Affairs: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support|Spero Therapeutics: Grant/Research Support.